Trends in consumption of vegetable edible oils in India: A temporal analysis: Trends in consumption of vegetable edible oils in India: A temporal analysis - D VAISHNAVI SANKARI; S V RAMANA RAO; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
Though India is one of the largest producers of oilseeds in the world, it is the biggest vegetable oil importer to meet the supply demand imbalance thus causing a huge loss to the exchequer of the nation. The present per capita consumption is 18.2 kg/annum. The growth analysis suggested that during the TMO period, highest rate of growth of area, production was evidenced. Population growth rate, domestic oil availability and out of home consumption, are observed to be the main factors for higher imports of edible oils. Appropriate policy on import duty of edible oils and increase in MSP for oilseeds and its implementation may encourage domestic production of edible oils thereby reducing the import bill.